Child Discipline Development at the Aisyiyah Grogol Sukoharjo Girls' Orphanage - Haning, Nahzaniya Nur; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Orphanages function as social institutions where in their daily lives, children are cared for, educated, guided, directed, given affection, provided with daily needs and given skills. The purpose of this study is to describe the forms of discipline and participation development of children at the Aisyiyah Grogol Sukoharjo Orphanage. This type of qualitative research was conducted at the Aisyiyah Grogol Sukoharjo Orphanage on December 1-4, 2025. The sources of this study were the head of the Aisyiyah Grogol Sukoharjo Orphanage, Mrs. Siti Parini, and the orphanage caretaker, Umi Aminah. Data collection techniques were through interviews, observation, and documentation. The results of the study are that (1) The forms of discipline development at the Aisyiyah Grogol Sukoharjo Orphanage include congregational prayers on time, on duty on time. (2) Participation of orphanage children in disciplinary development at the Aisyiyah Grogol Sukoharjo Orphanage for Girls through daily activities, religious development, and character development of orphans.